Towards a critical epidemiology approach for applied sexual health research. (February 2018) - Edelman, Natalie
Critical approaches may benefit epidemiological studies of sexual health. This article proposes a critical approach, reconcilable with social epidemiological enquiry. Key aims of critical epidemiology for sexual health are identified, from which three criticisms of practice emerge: (1) lack of attention to socio-cultural contexts, (2) construction of 'risk' as residing in the individual and (3) enactment of public health agendas which privilege and pathologise certain behaviours. These reflect and construct an apolitical understanding of population health. This article proposes features of a critical epidemiology that represent a morally driven re-envisioning of the focus, analysis and interpretation of epidemiological studies of sexual health.